The Effect of Presenteeism on Productivity Loss in Nurses: The Mediation of Health and the Moderation of General Self-Efficacy - Li, Yongxin; Zhang, Jihao; Wang, Shengnan; Guo, Shujie (Frontiers in Psychology, 2019)
Background: 74% of Chinese employees have experienced working with illness, but limited number of researchers have paid attention on this phenomenon. Most of the previous research on presenteeism has almost exclusively focused on North America and Europe, and have gone to the financial emphasis. The current researches have two shortages, which are laying in the consensus on the definition and measurement of presenteeism, as well as the mechanism of presenteeism and its outcomes, have set barriers for scholars to generate deeper understanding of the behavior. The aim of the present study was to explore the current situation of presenteeism among Chinese nurses and the mediating effect of health and the moderating effect of general self-efficacy between presenteeism and productivity loss. Methods: Data were collected from a A sample of 340 female nurses from a 3A-graded general hospital in Henan Province, China by using the Sickness Presenteeism Questionnaire (SPQ), the Stanford Presenteeism Scale (SPS-6), the 12-item General Health Questionnaire (GHQ-12) and the General Self-Efficacy Scale (GSES). Results: The results indicated that the mean of SPQ was 3.2 ± 0.7 in this sample, and there were significant differences in age and marital status in SPQ scores. Presenteeism was positively significantly associated with health and productivity loss, and health was positively significantly associated with productivity loss, and general self-efficacy was negatively associated with productivity loss. A bootstrap test showed that health fully mediated the relationship between presenteeism and productivity loss in nurses. Hierarchical regression analysis confirmed the moderating role of general self-efficacy between presenteeism and productivity loss. Conclusions: Presenteeism can significantly predict productivity loss in nurses, and hospital management can improve the physical and mental health of nurses and enhance their self-efficacy level to reduce the negative impact of presenteeism on productivity loss.